2021
DOI: 10.1186/s12873-021-00521-4
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte distribution width (MDW) as a new tool for the prediction of sepsis in critically ill patients: a preliminary investigation in an intensive care unit

Abstract: Background Monocyte Distribution Width (MDW), a simple proxy marker of innate monocyte activation, can be used for the early recognition of sepsis along with Procalcitonin. This study explored the added value of MDW as an early predictor of ensuing sepsis in patients hospitalised in an Intensive Care Unit. Methods We performed an observational prospective monocentric study to estimate the analytical performance of MDW in detecting ensuing sepsis in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Among them, MDW deserves to be presented in more detail. MDW is a novel haematological parameter recently introduced for the diagnosis of sepsis [18,27], which has been already targeted by recent investigations [28]. Our study confirmed a significant association between MDW and sepsis [29][30][31], consistently with other viral diseases [29,30,32].…”
Section: Discussionsupporting
confidence: 82%
“…Among them, MDW deserves to be presented in more detail. MDW is a novel haematological parameter recently introduced for the diagnosis of sepsis [18,27], which has been already targeted by recent investigations [28]. Our study confirmed a significant association between MDW and sepsis [29][30][31], consistently with other viral diseases [29,30,32].…”
Section: Discussionsupporting
confidence: 82%
“…The system furthermore calculates the means and standard deviations of these groups’ cell morphometric parameters [ 22 ]. The manufacturer of the hematology analyzer did not offer the unit for MDW, as previously reported [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the MDW values were significantly higher at the time of clinical sepsis diagnosis than at admission. In addition, Polilli et al 41 compared patients with no sepsis, sepsis, and septic shock and found that MDW values were significantly higher in patients with sepsis or septic shock than in the no sepsis group [median 26.23 (IQR: 23.48–29.83); 28.97 (IQR: 21.27–37.21); 21.99 (IQR: 19.86–24.36)]. Moreover, the elevation of MDW was independent of the type of sepsis-causing pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of MDW > 23 and PCT > 0.5 ng/mL had high specificity (92.6%), Youden index (0.61) and PPV (92.6%). 41 Therefore, the combination of MDW with other inflammatory indicators (PCT, CRP, interleukin, and leukocyte-related indicators) indicates a great potential for early diagnosis and prediction of sepsis prognosis.…”
Section: Introductionmentioning
confidence: 99%